SKRINING FITOKIMIA DAN POTENSI ANTIBAKTERI EKSTRAK ETANOL DAUN SIRIH HUTAN (Piper aduncum L.) TERHADAP BAKTERI Escherichia coli DAN Staphylococcus aureus : A MINI REVIEW - Sanjaya, I Made Duwi; Purba, Ritson; Saleh, Chairul (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Sirih hutan is a plant that belongs to the genus Piper and is found in many tropical areas, especially in tropical Asia. Sirih contains essential oils composed of betlephenol, cavikol, sesquiterpenes, hydroxycavikol, cavibetol, estragol, eugenol, and carvakrol which against Gram positive bacteria and Gram negative bacteria. Antibacterial activity test of ethanol extract of sirih hutan (Piper aduncum L.) has been conducted. This study aims to determine secondary metabolite compounds contained in sirih hutan leaves and potential as antibacterials, determined using the disc diffusion method. From the results of phytochemical tests, secondary metabolite compounds contained in sirih hutan are obtained in the form of alkaloids, steroids, phenolics, flavonoids, tannins, quinones and saponins. The results of the literature showed that sirih hutan leaf ethanol extract had antibacterial activity with the highest concentration used at 60% and the diameter of the inhibitory zone formed in Escherichia coli and Staphylococcus aureus was 14 mm. Keywords : Antibacterial, Forest Betel, Phytochemical Screening